Sustainable and intensive cropping systems for humid ecologies of South-Eastern Rajasthan - J.P. Tetarwal; Baldev Ram; R.K. Nagar; G.R. Choudhary (Annals of Agricultural Research, 2022)
A field experiment was conducted at Agricultural Research Station, Ummedganj, Kota, Rajasthan, India during six consecutive years (2009-10 to 2014-15) to find out the most sustainable and intensive cropping systems for humid ecologies of South Eastern Rajasthan. The experiment comprised eight cropping systems in a randomized block design with three replications. The study revealed that maize-garlic cropping system was recorded maximum production efficiency (50.62 kg ha–1day–1), relative production efficiency (150.85 %), system productivity (11552 kg ha–1), net returns (Rs. 214069 ha–1), system profitability (Rs. 586.49 ha–1 day–1) and relative economic efficiency (171.90 %) followed by soybean (broad bed) + maize (furrow)-garlic (broad bed) + wheat (furrow) and maize + blackgram (1:1)-gram + linseed (6:1)-cowpea (vegetable + residue) cropping system. The maximum land use efficiency (76.39 %) and B:C ratio (3.28) were observed in maize + blackgram (1:1) - gram + linseed (6:1)-cowpea (vegetable + residue) cropping system. Thus, the intensive and diversified cropping systems were observed more productive and remunerative system compared to existing dominant soybean-wheat cropping system in humid ecologies of south-eastern Rajasthan.